THE MANUAL OF WATER WORKS ACCOUNTING. - Tenner, Irving (The Accounting Review, 1939)
This article points out the features of "Manual of Water Works Accounting," prepared jointly by the Municipal Finance Officer's Association and the American Water Works Association. Budgetary statements are an essential part of any municipal report That municipal officers have a duty to inform the public that they have complied with the provisions of the budget is now unques- tioned. Finally statistical statements are in some respects as important if not more important for the public than balance sheets or income statements for several reasons: They are easy to understand; they present a mass of valuable information in concise form; they present some evidence of the efficiency with which officials are carrying on operations; and they show trends. Many of the journal entries will be useful to officials who have a good knowledge of accounting but who are not familiar with utility accounting. It is for the benefit of the latter class of officials that some of the more complicated aspects of water works accounting were presented.